2007
DOI: 10.1111/j.1365-2842.2007.01743.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between food mixing ability and mandibular movements during chewing of a wax cube

Abstract: The purpose of this study was to clarify whether masticatory movements during chewing of a wax cube associate with food mixing ability. Twenty-six dentate subjects (mean age 25.3 years) were directed to chew a two-coloured paraffin wax cube for 10 strokes on preferred chewing side. Mixing Ability Index (MAI) was determined from the colour mixture and shape of the chewed wax cube. MAI was employed as an estimate of food mixing ability. Mandibular movements during chewing of the wax cube were recorded using a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 40 publications
3
57
2
2
Order By: Relevance
“…Furthermore, some other parameters of mandibular movement, such as vertical amplitude, cycle duration and closing duration, were significant correlated with food mixing ability, being the former a positive and the other 2 parameters, negative correlations (5). The closing path was also associated to quality of mastication, being the closing angle negatively correlated with food mixing ability (5) and a convex closing path related to better masticatory function (6).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Furthermore, some other parameters of mandibular movement, such as vertical amplitude, cycle duration and closing duration, were significant correlated with food mixing ability, being the former a positive and the other 2 parameters, negative correlations (5). The closing path was also associated to quality of mastication, being the closing angle negatively correlated with food mixing ability (5) and a convex closing path related to better masticatory function (6).…”
Section: Introductionmentioning
confidence: 85%
“…function. Previous studies have used different materials, with distinct characteristics, number of particles, size and weight, for analysis, such as wine gum, almond, paraffin, wax cube, gummy jelly (4)(5)(6)(7)(8), while the present study used cubes made of a rubber based artificial material. It has been reported that chewing cycle alters its pattern according to the hardness or the size of bolus (3) and to the rheological properties of the food (15), suggesting the reason for such divergence of data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each chewing cycle was identified from the starting time of an opening phase (the end of a previous occlusal phase) until the end of the next occlusal phase, as previously described. 19 After identification, chewing strokes were analyzed laterally and each cycle was determined as right, left or bilateral according to the lateral position during the occlusal phase of a given stroke. To present unilateral mastication or a preferred chewing side, the participant was required to perform 80% of the strokes coinciding on one side, 20 i.e., twelve out of fifteen chewing strokes.…”
Section: Determination Of Preferred Chewing Sidementioning
confidence: 99%
“…Mandibular movement variables have been associated with masticatory performance. Better masticatory performance has been related to greater vertical mandibular range of motion, higher closing velocity, and shorter duration of the masticatory cycle closing phase (15,16) . The study of the behavior of the kinematic variables of deliberate unilateral and habitual mastication in healthy individuals can contribute to the understanding of the possible impact of the pattern adopted on masticatory performance in cases of disorders that interfere with the chewing function, such as TMD, oral breathing, and occlusal alterations.…”
Section: Introductionmentioning
confidence: 99%